Recyclable Heterogeneous Fe-Mo Nanocatalyst: Application in Solvent Free Synthesis of β-enaminones - Bankar, Swapnil R. (Current Organocatalysis, 2019)
Background: In recent years, green organic transformation has become a challenge for a chemist in areas like social sector, health, and environment. Literature survey revealed that a nano magnetite supported heterogeneous catalysis is an emergent field with huge application in chemical synthesis. Objective: In the present article, the aim was to develop a simple and facile method to carry organic reaction under benign media. So, the focus was on the synthesis of nano-magnetite supported molybdenum catalyst and its application in β-enaminones synthesis. Methods: Magnetically recyclable heterogeneous ferrite-molybdenum catalyst was prepared by simple impregnation method. The synthesized nanocatalyst Fe-Mo was well analysed by spectroscopic techniques like X-ray diffraction analysis, X-ray photoelectron spectroscopy, transmission electron microscopy, field-emission gun scanning electron microscopy and vibrating-sample magnetometry. The functionalized nanocatalyst Fe-Mo was employed in the synthesis of β-enaminones under solvent free condition. Results: The competency of synthesized nanocatalyst-Fe-Mo was observed to be good for the synthesis of β-enaminones derivatives under microwave irradiation and gave excellent yield (86-96%) of the product. The catalyst was recycled for more than five consecutive runs without significant loss in its activity. Conclusion: In the present research article, synthesis of highly active, magnetically recyclable Fe- Mo nanocatalyst was obtained from easily available precursor. The MNP was stable under investigated conditions and effective in β-enaminones synthesis. The simple eco-friendly method, low catalyst loading, short transformation time, and reusability of the catalyst thoroughly follow the sustainable protocol.
Keywords: magnetic nanocatalyst-Fe-Mo